Perturbações do Comportamento Alimentar e Gravidez - Revisão Sistemática - Joana Pereira Lourenço (2022)
Introduction: Physical and psychological changes occur during pregnancy, which may modify the pregnant woman's own body perception. The existence of a history of eating disorders is associated with a higher risk of an inadequate intake of nutrients. Therefore, it is essential to understand the impact of these disorders during pregnancy. Methods: The study was performed following PRISMA guidelines. The articles were searched in 3 databases: PubMed, Scopus and Web of Science. Risk of bias was assessed by using National Institutes of Health criteria. Results: The initial search resulted in 4190 articles, 23 of which were included in the review. The most prevalent outcomes observed in women with past or current eating disorders were the presence of nausea, vomiting, anemia and anxiety symptoms. Some studies have also described lower cortisol levels, increased likelihood of preterm birth and low birth weight newborns. Conclusion: There are several negative pregnancy outcomes related with eating disorders. However, in the future it will be important to further explore the consequences associated with each disorder and to study populations with different characteristics.